2020
DOI: 10.2217/pme-2019-0100
|View full text |Cite
|
Sign up to set email alerts
|

Review of Policies of Companies and Databases Regarding Access To Customers’ Genealogy Data for Law Enforcement Purposes

Abstract: The rapidly evolving popularity of direct-to-consumer genetic genealogy companies has made it possible to retrieve genomic information for unintended reasons by third parties, including the emerging use for law enforcement purposes. The question remains whether users of direct-to-consumer genetic genealogy companies and genealogical databases are aware that their genetic and/or genealogical data could be used as means to solving forensic cases. Our review of 22 companies’ and databases’ policies showed that on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 20 publications
0
20
0
Order By: Relevance
“…As of 2019, there have been more than 26 million SNP profiles generated by the DTC companies, and the number is increasing [70]. In addition, there are at least 22 individual genealogy databases in the United States and Europe alone [71]. One of the most widely used databases for forensic investigations is GEDMatch, which allows users to voluntarily upload their DNA profiles primarily to find relatives.…”
Section: Databases and Searching Effectivenessmentioning
confidence: 99%
See 1 more Smart Citation
“…As of 2019, there have been more than 26 million SNP profiles generated by the DTC companies, and the number is increasing [70]. In addition, there are at least 22 individual genealogy databases in the United States and Europe alone [71]. One of the most widely used databases for forensic investigations is GEDMatch, which allows users to voluntarily upload their DNA profiles primarily to find relatives.…”
Section: Databases and Searching Effectivenessmentioning
confidence: 99%
“…Users may have the option to opt in or out for law enforcement searches, depending on the policies of the databases. A recent review of the policies of 22 genealogy companies and databases showed that only 4 provided their policies on law enforcement agencies access to their services [71]. The limits and consequences of privacy protection are, thus, very different between forensic databases and IGG databases.…”
Section: Privacy Concernsmentioning
confidence: 99%
“…Furthermore, 23andMe, Ancestry, and Helix provide a transparency report in which they summarize all law enforcement and/or governmental requests they received. Among the 22 companies and databases, FamilyTreeDNA and GEDmatch do not require different formal requests to provide information to law enforcement (Skeva, Larmuseau, and Shabani 2020).…”
Section: The Advent and Consolidation Of Long-range Familial Searchesmentioning
confidence: 99%
“…In the absence of legal precedence, companies holding recreational DNA databases, therefore, raise clear questions about accountability, ownership of data, and infringements of citizens' rights. The transnational nature of such databases, as companies provide services in several countries, complicates this scenario even further (Skeva, Larmuseau, and Shabani 2020;Thomson et al 2020). Long-range familial searches in recreational DNA databases are mainly taking place in the USA.…”
Section: The Advent and Consolidation Of Long-range Familial Searchesmentioning
confidence: 99%
See 1 more Smart Citation